A Mapping Research Trends in Material Science Analysis for Automotive Emission Control: A Global Bibliometric Study - *, Bintang; Mutiara, Tasya Dewi; Setiawan, Ryu Arfan (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2026)
This study aims to map the development and research trends in the field of material science for automotive emission control through a bibliometric analysis approach. Data were obtained from the Scopus database, consisting of 413 documents published between 2021 and 2026, limited to the Materials Science subject area and English-language publications. The analysis employed VOSviewer software to identify collaboration patterns, keyword distributions, and major research themes. Results indicate that research is dominated by topics such as automotive industry, emission control, greenhouse gases, and life cycle assessment. The publication trend remains stable with a growing emphasis on sustainability and energy efficiency. Overall, this study highlights the crucial role of material science in supporting the development of cleaner, more efficient, and environmentally friendly automotive technologies.